IDENTIFICATION OF COMPLEX ORGANIC MOLECULES IN THE HOT MOLECULAR CORE G335.79+0.17 - Abdirakhman, A.A.; Omar, A.Zh.; Alimgazinova, N.Sh.; Tuiakbayeva, D.R.; Baitursyn, D.Y. (Eurasian Physical Technical Journal, 2026)
Observations of the massive star-forming region G335.79+0.17 reveal dense, hot molecular gas toward two cores, P1 and P2, traced by methyl cyanide, its isotopologue, methyl acetylene, formaldehyde and dust continuum emission. Only these two hot cores are detected, highlighting a chemically rich environment typical of early massive star formation. Velocity gradients in opposite directions provide strong evidence of molecular gas rotation. Rotational diagram analysis shows that core P1 is hotter than P2, with methyl cyanide and its isotopologue tracing gas near the protostar, while methyl acetylene traces cooler outer layers.